Laughter as a Semiotic Problem - Vershyna, V. A.; Mykhailiuk, O. V. (Anthropological Measurements of Philosophical Research, 2021)
Purpose. The article is aimed to substantiate the view on the phenomenon of laughter as a subject of semiotic analysis, which leads to the following tasks: to reveal the possibilities of semiotics application in the study of laughter nature; to analyze the phenomenon of laughter as a cultural and natural phenomenon, as a sign and as an attribute; to consider the place of laughter in culture, which is understood as a sign system. Theoretical basis. The semiotic approach proceeds from the fact that human lives in the world of signs, all the surrounding reality can be interpreted as a sign system. The basic concept of semiotics is the concept of a sign. The theoretical basis of the article is understanding the culture as a sign-symbolic system. Laughter is considered as a phenomenon ontologically rooted in human culture. At the same time, laughter is on the edge of culture. The research is based on the work of semiotic authors, cultural researchers, and the researchers of laughter. Originality. The originality lies in the application of the semiotic method to the research of laughter phenomenon, consideration of the dialectics of natural and cultural, signedness and non-signedness, manifested in the phenomenon of laughter. Conclusions. Laughter is considered as a psychophysiological phenomenon (attribute) and as a cultural phenomenon (sign). Laughter acts as an emotional manifestation, a physiological reaction, but socially and culturally mediated. In any case, laughter indicates an emotional or cognitive state of a human. Laughter acts as a process and result of the interpretation of a sign, a reaction to a sign. Laughter is a form and a means of communication. Being a natural phenomenon, in the process of social evolution, laughter acquires signedness, is integrated by culture as a sign system, and, at the same time, maintains a connection with nature. Thus, laughter occupies an ambivalent position between nature and culture. In the phenomenon of laughter, the dual state of human is revealed. In laughter, boundaries are blurred, the unity and opposition of natural and cultural, biological and social, soul and body, thought and feeling, sign and attribute are manifested.